PENGARUH BERAT BENIH DAN MEDIA TANAM TERHADAP PERTUMBUHAN VEGETATIF BIBIT DURIAN (Durio Zibethinus Murr) - Ding, Tomas; Sutejo, Hery; Fatah, Abdul (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
Effect of  Seed Weight and Growing Media on the Vegetative of  Durian Seedling (Durio zibethinus Murr).  The research aimed at knowing the effect seed weight and growing media on the vegetative growth of Durian seedling.  It lasted for about four months, from February to May 2013, and carried out at Ujoh Village of Long Bagun Sub District, Mahakam Ulu Regency. The Completely Randomized Design was employed for the research with repetitions.  The first factor was seed weight (B) that consisted of 3 sub-factor 7-12 g (b1), 14-17 g (b2), and 18-20 g (b3).  Whereas the second factor was growing media (M) : entirely top soil (m1), equal mix 1:1 between top soil and sand (m2), equal mix 1:1 between top soil and cow dung (m3), and equal mix 1:1 between top soil and paddy straw (m4).  Result of the research revealed that : (1) the seed weight affected very significantly on the seedling height at 30, 60 and 90 days, leave number at 60 and 90 days and stem diameter at 30, 60 and 90 days.  But it did not affect significantly on the leave number 30 days.  (2) the growing media affected very significantly on seedling stem diameter at 90 days, affected significantly on seedling height at 90 days, but did not affect significantly on seedling height at 30 and 60 days, leave number at 30, 60 and 90 days, and stem diameter at 30 and 60 days, and (3) the interaction between the two above factors did not affect significantly on all parameters observed.